2019
DOI: 10.1016/j.ssmph.2019.100350
|View full text |Cite
|
Sign up to set email alerts
|

Investigating site-level longitudinal effects of population health interventions: Gay-Straight Alliances and school safety

Abstract: There is limited research on evaluating nonrandomized population health interventions. We aimed to introduce a new approach for assessing site-level longitudinal effects of population health interventions (SLEPHI) by innovatively applying multiple group multilevel (MG-ML) modeling to repeated cycles of cross-sectional data collected from different individuals of the same sites at different times, a design commonly employed in public health research. For illustration, we used this SLEPHI method to examine the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Some of these positive effects have been observed not just in SMY youth but in heterosexual adolescents as well. [65][66][67][68]…”
Section: Discussionmentioning
confidence: 99%
“…Some of these positive effects have been observed not just in SMY youth but in heterosexual adolescents as well. [65][66][67][68]…”
Section: Discussionmentioning
confidence: 99%
“…Promoting healthy romantic relationships, both for SMY and heterosexual youth, may reduce (romantic) stress and have a positive impact on peer norms. Direct measures to promote health and resilience in SMY, such as ‘gay-straight alliances’ or ‘gender-sexuality alliances’ [70], media-based interventions to address sexual orientation related prejudice [71] or introducing safe school policies [72] have a documented beneficial effect on the health of not just SMY, but on heterosexual adolescents as well. Risk prevention and enhancing resilience and well-being in SMY should be part of national youth health strategies [73].…”
Section: Discussionmentioning
confidence: 99%
“…Future research should investigate associations between longitudinal trends in bullying and attitudes toward sexual and gender minority persons in US politics. Further, policies explicitly protecting SMY have been associated with fewer suicide attempts and fewer physical and emotional stressors (Hatzenbuehler et al, 2014;Li et al, 2019;Meyer et al, 2019;Saewyc et al, 2014), and a protective school climate has been found to associate with the same, as well as with improved academic performance (Birkett et al, 2009;Kosciw et al, 2015;Kosciw et al, 2013). Consequently, understanding the impact of bullying and bullyingrelated victimization among SMY, particularly as they relate to political climate and policy interventions (Murchison et al, 2019), may help identify avenues for intervention to decrease weapon carrying among SMY.…”
Section: Discussionmentioning
confidence: 99%
“…It is important therefore to ask not only how we may reduce rates of bullying but also how to promote safe and supportive environments for SMY at all levels (Birkett et al, 2009; Saewyc et al, 2014). The presence of gender and sexuality alliances (GSAs) in schools has been associated with reductions in bullying and concomitant increases in both sexual minority and heterosexual students’ sense of perceived safety (Li et al, 2019; Saewyc et al, 2014). Establishing a protective climate for SMY in schools by advocating for GSAs or other school-based anti-bullying and stigma reduction interventions may therefore not only improve health and scholastic outcomes (Marx & Kettrey, 2016) but also reduce the risk of weapon carrying and inevitable disciplinary intervention (Kosciw et al, 2015).…”
Section: Implications For Pediatricians Parents and School Personnelmentioning
confidence: 99%